Pale halo surrounding a homogenous bluish-purplish central area: dermoscopic clue for eccrine hidrocystoma - Nilay Duman; Deniz Duman; Sedef Sahin (Mattioli1885, 2015)
Abstract Eccrine hidrocystomas are benign tumors of the sweat glands that arise from cystic dilatation of the excretory sweat duct. Exact diagnosis requires biopsy and histopathologic examination, from which arises risk of scarring. Dermoscopy could be a useful tool in diagnosing eccrine hidrocystomas. Herein we aim to present dermoscopic features in three female patients with multiple lesions on the face consistent with eccrine hidrocystomas.